Delineating agritourism: insights from Gujarat India / Yash Padhiyar… [et.al] - Padhiyar, Yash; Shukla, Yupal; Purohit, Rajen (Universiti Teknologi MARA Cawangan Sarawak, 2016)
The present research identifies and proposes a delineation that defines agritourism by rectifying the key characteristics presently used to define agritourism in the literature. Efforts are put towards organizing them into a visible and constructed framework. The study highlights a proper understanding of agritourism as an economic tool which can help to support and satisfy both tourists, and farming fraternity. The cadre-1 officers of a renowned agricultural university from Gujarat were interviewed and data was evaluated to consolidate validity. Local culture and traditional ways of learning are drawn upon to explain knowledge sharing and practical learning which can be derived through empirical research to know the viability of the proposed delineation about agritourism. The key finding in the paper is the classification pertaining to delineation of agritourism through different labels and interview processes in the Gujarat context. The unique feature of the concept implication of agritourism is in its ability to fulfill the space between the practice and theory. It also helps to support framework to underpin academic research of the phenomenon and has the capacity to harness more practical study on the difference between agritourism kinds. The research serves as an illustration of viable development that could be replicated through agritourism in rural settings as an economic empowerment tool.